Facial video photoplethysmography for measuring average and quasi-instantaneous heart rate: a pilot validation study - Pstras, Leszek; Okupnik, Tymoteusz; Ponikowska, Beata; Paleczny, Bartlomiej (Frontiers in Physiology, 2025)
BackgroundVideo photoplethysmography (vPPG) is a contactless optical technique for recording blood pulsations in the blood vessels of the skin using a digital camera that is increasingly used to measure or estimate various physiological parameters. In this study, we evaluated the accuracy of average and quasi-instantaneous heart rate (HR) measurements performed via facial vPPG technology Shen.AI Vitals and a smartphone camera.MethodsWe studied 35 healthy volunteers in a seated position (median age 25 years, 17 females). Video recordings of participants’ faces were obtained using the front camera of a smartphone mounted on a tripod. In parallel, a 1-lead chest electrocardiogram (ECG) was recorded to obtain reference HR values (average value from the entire 60-s measurement and multiple values averaged over 10-s or 4-s periods during the measurement).ResultsThe mean absolute errors were 0.1, 0.2, and 0.4 beats per minute (bpm) for HR averaged over 60-s, 10-s, and 4-s periods, respectively. The errors did not exceed 1 bpm in 100.0%, 99.8%, and 94.5% of the cases, respectively. For the latter, our sample included almost 1,900 HR values from a relatively wide range (46–117 bpm). Regardless of the HR averaging time, the correlation between the vPPG-based and reference values was very strong (r > 0.99, P < 0.001).ConclusionIn predominantly young, white, seated subjects, the tested vPPG technology provided highly accurate HR measurements, both when the values were averaged over 60 s and in the case of short-term values averaged over 10 s or quasi-instantaneous values averaged over 4 s. To our knowledge, this is the first study on vPPG technology to examine quasi-instantaneous HR measurements (averaged over periods shorter than 5 s). The results should be confirmed in a larger study with greater diversity in age, skin tone, and lighting conditions.